A Calm mom–baby happy: utilizing lemongrass peel aromatherapy to treat baby blues syndrome in postpartum mothers - Raffiky Sustamy; Wiwik Muhidayati (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: In Indonesia, the prevalence of Baby Blues Syndrome is relatively high. The Ministry of Health (2023) reported an incidence rate ranging from 50%–70%, or approximately 1–2 cases per 1,000 births. Furthermore, data from the National Population and Family Planning Agency shows that approximately 57% of mothers experience symptoms of baby blues, making Indonesia one of the countries with a high prevalence in Asia. If left untreated, this condition can negatively impact the mother-baby relationship and increase the risk of postpartum depression. The "Calm Mom – Baby Happy" innovation utilizes a combination of orange peel and lemongrass aromatherapy as a non-pharmacological intervention. Purpose: To determine the effectiveness of orange peel and lemongrass aromatherapy in reducing the level of baby blues syndrome symptoms in postpartum mothers in Dander District. It provides a relaxing effect. Method: This study used a quasi-experimental design with a pre-test and post-test control group design. The study population was postpartum mothers in the Dander Community Health Center (Puskesmas) area, with a sample of [insert number] respondents drawn through a purposive sampling technique. The level of baby blues was measured using the Edinburgh Postnatal Depression Scale (EPDS). The intervention consisted of 15 minutes of aromatherapy inhalation daily for one week. Results: Statistical analysis using the Wilcoxon Signed Rank Test showed a significant decrease in EPDS scores after the intervention (p-value <0.05). Before the intervention, the majority of respondents were in the moderate to high-risk category for baby blues, while after the intervention, most respondents experienced reduced nervous tension and reported better sleep quality. Conlusion: Orange peel aromatherapy, rich in limonene, works to suppress the sympathetic nervous system, while the citral content in lemongrass has a mild sedative effect. Inhalation through the limbic system stimulates the release of endorphins and serotonin, which create a sense of calm. This proves that the combination of these two local ingredients is effective in stabilizing the emotions of postpartum mothers without any medical side effects. Suggestion: This method is recommended as a self-help therapy at home for postpartum mothers in Dander District to improve maternal mental well-being and the quality of infant care.